MANAJEMEN PENDIDIKAN MAMPU MENINGKATKAN EKONOMI USAHA KECIL - Cahyanti, Lisa Suci (Jurnal Likhitaprajna, 2017)
Education, productivity & Growth of economy are interrelated variabel. Education in a facility and main strategic to devlope human resources. By this education will support to some one higher knowligde, skill & prundent higher educated poeple will produce qualified goods & service and will be appresiated by some one else. This is important points increase growth of economy in a country. Small business as an economic activity of society on a small scale, has a central role in the economy of indonesia. AlthoughÂ  the economic crisis has created a greated a gread distribance in the live of lerge and middle-size business, apparently small business countinues to function well in the lower levels of the economy. The main role of small business is: (1) use excess labor; (2) as a producer of goods and services at reachable prices for the lower economic level of society; (3) as a potential producer of foreign exchange because of the success of this type of industry in producing non-oil commodities for export. Remembering that the role of small business is large and has great influence of the lower economic levels of society, it is quite necersary to pay attention to the development of the sector.Key words: education, productivity, small business